MODERN APPROACHES TO THE STUDY OF CYBERSECURITY AND CYBER HYGIENE IN THE FRAMEWORK OF DIGITAL TRANSFORMATION OF SOCIETY - FEDUSHKO, SOLOMIIA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
In today’s digital society, cybersecurity and cyber hygiene have become crucial for safeguarding individuals, organizations, and states from cyber threats. This scientific paper discusses the significance of cyber hygiene and cybersecurity research, which involves developing new methods to protect information technology and educating users on the importance of cybersecurity. The paper highlights the consequences of negative digital technology impacts on human health and the environment and emphasizes the need to develop prevention methods. Good cyber hygiene practices such as changing passwords regularly, using antivirus software, and avoiding suspicious websites can prevent unauthorized access to sensitive information and reduce the spread of malware and viruses. This study stresses the importance of maintaining cyber health for the integrity of computer systems and networks. This paper aims to emphasize the importance of cyber hygiene and cybersecurity in modern society and promote good cyber hygiene practices to protect individuals, organizations, and states from cyber threats. This paper provides a comprehensive overview of cyber hygiene and cybersecurity research, which is increasingly relevant in today’s rapidly developing technological world. The paper highlights the consequences of negative digital technology impacts on human health and the environment, emphasizing the need for developing prevention methods. Additionally, the paper emphasizes the importance of cybersecurity at the cultural and educational levels to ensure protection against cyber threats. This paper provides practical recommendations for individuals and organizations to practice good cyber hygiene, including changing passwords regularly, using antivirus software, avoiding suspicious websites, keeping software up to date, and avoiding opening suspicious emails or attachments. Implementing these practices helps protect sensitive information, prevent the spread of malware and viruses, and maintain the overall integrity of computer systems and networks.